Development of Local-Based MSMEs in Encouraging the Economy of Aisyiyah Candinegoro Branches - A, M Rayhan; I, Mariza; H, Lutfia; Marcelino, Marcelino; Sari, Herlinda Maya Kumala (Universitas Muhammadiyah Sidoarjo, 2025)
During the KKN Real Work Lecture, they carried out an activity program for making MSME products, namely Banana Chips. This activity aims to encourage Aisyiyah branches in Candinegoro to increase potential and the economy. This method uses discussion and explanation of the problems in the research carried out, in order to obtain relevant data for further discussion. This research is intended to obtain a comprehensive picture of the development of Micro, Small and Medium Enterprises. When the production process is carried out, it is quite simple in terms of marketing. This product is packaged using ziplock plastic and a jar as well as the product design. In real work study activities, as students who are carrying out real work study activities, you can provide counseling and assistance to these MSMEs. This activity process can increase knowledge and benefits for the Aisyiyah Candinegoro branch in developing the business.